A Decentralized and Connected Health System Business Plan - Nikolaus Permana Tri Rahmanto, Gunawan Wang (International Journal of Advanced Science and Technology, 2020)
Health problems are challenges that will always be faced by every country. At present health services face challenges in the form of lack of medical services and health care providers coupled with uneven distribution, health problems are also increasingly complex, resulting in the need for an adequate health care system [1]. The number of doctors in Indonesia is also inadequate, with a ratio of three doctors per 10,000 population, not comparable to Singapore which has 25 to 28 doctors for 10,000 population [2]. Another problem faced is the recording of medical records which is an important asset in the context of health services, especially in streamlining costs. A medical record is a source of data to determine the health profile that contains documents and records of patient identity, examination, care, services, and others. The different types of software, formats, and data dictionaries in each health facility are the main problems [3]. MedDApp [4] is a solution offered as a system to overcome health service problems in Indonesia. MedDApp exists to solve health problems with a focus on solving preventive problems in health. The purpose of this thesis is to look at the business opportunities that MedDApp has by making comprehensive business plans from the MedDApp system, using business tools such as Business Model Canvas, SWOT Analysis, 5 Forces porter's model and Financial Analysis